Insights into the Role of Tick Salivary Protease Inhibitors during Ectoparasite-Host Crosstalk - Jmel, Mohamed Amine; Aounallah, Hajer; Bensaoud, Chaima; Mekki, Imen; Chmelař, Jindřich; Faria, Fernanda; M'ghirbi, Youmna; Kotsyfakis, Michalis (International journal of molecular sciences, 2021)
Protease inhibitors (PIs) are ubiquitous regulatory proteins present in all kingdoms. They play crucial tasks in controlling biological processes directed by proteases which, if not tightly regulated, can damage the host organism. PIs can be classified according to their targeted proteases or their mechanism of action. The functions of many PIs have now been characterized and are showing clinical relevance for the treatment of human diseases such as arthritis, hepatitis, cancer, AIDS, and cardiovascular diseases, amongst others. Other PIs have potential use in agriculture as insecticides, anti-fungal, and antibacterial agents. PIs from tick salivary glands are special due to their pharmacological properties and their high specificity, selectivity, and affinity to their target proteases at the tick-host interface. In this review, we discuss the structure and function of PIs in general and those PI superfamilies abundant in tick salivary glands to illustrate their possible practical applications. In doing so, we describe tick salivary PIs that are showing promise as drug candidates, highlighting the most promising ones tested in vivo and which are now progressing to preclinical and clinical trials.
Keywords: transkriptom; klíšťata; proteases; Protease Inhibitors; Host-Parasite Interactions; Saliva; interakce hostitele a parazita; drug discovery; inhibitory proteas; Ticks; Transcriptome; Salivary Glands; protease inhibitors; tick saliva; Animals; lidé; Humans; zvířata; sliny; slinné žlázy